1990
DOI: 10.1002/path.1711600306
|View full text |Cite
|
Sign up to set email alerts
|

Do AgNOR counts reflect cellular ploidy or cellular proliferation? A study of trophoblastic tissue

Abstract: There is considerable debate as to whether AgNOR counts reflect cellular ploidy or cellular proliferation. Trophoblastic tissue from hydropic abortions and from hydatidiform moles offers an excellent model for analysing this problem. Thus, complete moles show considerable cell proliferation but are diploid, whilst partial moles show markedly less cell proliferation but are triploid: hydropic abortuses are diploid and show no cellular proliferation. AgNOR counts in villous cytotrophoblastic cells from hydropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

1991
1991
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…The prognostic significance of AgNOR counts may be due to their correlation with cell proliferation: in non-Hodgkin's lymphoma (Hall et al, 1988) and breast carcinomas there is a clear correlation between AgNOR staining and Ki67 immunostaining; cells positive for Ki67 have high AgNOR counts, while Ki67 negative cells contain only one or two AgNORs (Murray et al, 1989); a linear relationship was found between cell duplication activity and the amount of AgNOR proteins in cell lines derived from different tumour types (Derenzini et al, 1990). However, in renal cell carcinomas such correlation is only slightly significant (Pich et al, 1991) and in non-neoplastic tissues AgNOR counts seem to reflect a ploidy rather than cell proliferation (Suresh et al, 1990).…”
Section: Discussionmentioning
confidence: 81%
“…The prognostic significance of AgNOR counts may be due to their correlation with cell proliferation: in non-Hodgkin's lymphoma (Hall et al, 1988) and breast carcinomas there is a clear correlation between AgNOR staining and Ki67 immunostaining; cells positive for Ki67 have high AgNOR counts, while Ki67 negative cells contain only one or two AgNORs (Murray et al, 1989); a linear relationship was found between cell duplication activity and the amount of AgNOR proteins in cell lines derived from different tumour types (Derenzini et al, 1990). However, in renal cell carcinomas such correlation is only slightly significant (Pich et al, 1991) and in non-neoplastic tissues AgNOR counts seem to reflect a ploidy rather than cell proliferation (Suresh et al, 1990).…”
Section: Discussionmentioning
confidence: 81%
“…Significant differences of AgNOR counts are seen for pathological endometrium and neoplastic endometrium but siitc-absolute differences are small the use in any single case is limited (Hansen & Ostergard, 1990;Coumbe et at., 1988). In non neoplastic trophoblastic tissue AgNOR counts reflect ploidy and not proliferation (Suresh et al, 1990), thus apparently being unique in tissues so far studied; the reason for this is obscure. AgNOR counts may be useful in the diagnosis of borderline serous tumours of ovary but not in mucinous tumours Kinsey et al, 1988;Mauri et al, 1990 Egan et al, 1990).…”
Section: Genitourinary Systemmentioning
confidence: 99%
“…They are intimately related to the cell cycle (Goessens et al, 1987), and may be related to proliferation or ploidy in some circumstances (Suresh et al, 1990;Derenzini et al, 1989;Leek et al, 1990). During prophase the components of the fibrillar centre disperse and in metaphase these structures exist in constant positions on the short arms of the five acrocentric chromosomes (namely 13, 14, 15, 21 and 22).…”
Section: Physiology and Theoretical Basismentioning
confidence: 99%
“…This may be true of other clinical cancers although ploidy and cell proliferation are, in general, considered to be independent indicators, as shown by trophoblastic tissues. In this respect, both the close relationship between the AgNOR number and ploidy, and that between the AgNOR number and proliferative activity seem to be reasonable assumptions in clinical malignant lesions, while the AgNOR number has been proven to reflect the ploidy rather than proliferative activity in the ideal model like trophoblast (Suresh et al, 1990).…”
mentioning
confidence: 94%
“…On the other hand, studies of the breast lesions have suggested 4 5 that the AgNOR number was, at least partially, related to ploidy (Giri et al, 1989;Mourad et al, 1992). This problem was also carefully investigated by a study, using trophoblastic nbined group of tissues (Suresh et al, 1990 non-neoplastic trophoblastic tissues, the AgNOR number .1 was proven to be a reflection of ploidy rather than of cell proliferation.…”
mentioning
confidence: 99%